2021
DOI: 10.1126/scitranslmed.abg1210
|View full text |Cite|
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor drives pathology in a mouse model of spondyloarthritis and is associated with human disease

Abstract: Macrophage migration inhibitory factor produced by neutrophils worsens spondyloarthritis by inducing a pathogenic T H 17 phenotype in T regs .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 51 publications
0
21
1
Order By: Relevance
“…Macrophage migration inhibitory factor (MIF) is a multipotent cytokine involved in both inflammatory processes and anti-tumor immune response, having the properties of an enzyme, chemokine, and hormone simultaneously ( Sumaiya et al, 2021 ). As a proinflammatory mediator secreted by numerous immune cells, MIF promotes inflammation and autoimmune diseases mainly by binding with the receptor CD74 and co-receptor CD44, CXCR4, or CXCR2 ( Liehn et al, 2013 ; Nakamura et al, 2021 ; Wallace et al, 2021 ). Previous studies have shown that the carcinogenic role MIF plays is related to the activation of p53, Ras/MAPK, and Akt pathways in the inflammation–cancer axis ( Mittelbronn et al, 2011 ; Wang et al, 2017 ; Liu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage migration inhibitory factor (MIF) is a multipotent cytokine involved in both inflammatory processes and anti-tumor immune response, having the properties of an enzyme, chemokine, and hormone simultaneously ( Sumaiya et al, 2021 ). As a proinflammatory mediator secreted by numerous immune cells, MIF promotes inflammation and autoimmune diseases mainly by binding with the receptor CD74 and co-receptor CD44, CXCR4, or CXCR2 ( Liehn et al, 2013 ; Nakamura et al, 2021 ; Wallace et al, 2021 ). Previous studies have shown that the carcinogenic role MIF plays is related to the activation of p53, Ras/MAPK, and Akt pathways in the inflammation–cancer axis ( Mittelbronn et al, 2011 ; Wang et al, 2017 ; Liu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In affected patients subclinical gut inflammation, initiated by intestinal dysbiosis, is essential to the prospective development of inflammation in the synovial-entheseal complex. Although the crucial role of IL17/23 axis, TNF-α, and IL-7 in the pathophysiology of SpA, including JSpA, is well-known, the role of MIF is generally ignored, but recently validated (7,8) Along the same lines, Romero-López et al discuss the clinical and translational features of inflammatory foot involvement in SpA. The authors highlight the predominance of tarsal affection in JSpA patients among several cohorts.…”
Section: Overview Of the Issuementioning
confidence: 99%
“…In affected patients subclinical gut inflammation, initiated by intestinal dysbiosis, is essential to the prospective development of inflammation in the synovial–entheseal complex. Although the crucial role of IL17/23 axis, TNF-α, and IL-7 in the pathophysiology of SpA, including JSpA, is well-known, the role of MIF is generally ignored, but recently validated ( 7 , 8 ). The strong correlation of osteitis with low-grade IBD, established in children with ErA by elevated concentration of fecal calprotectin (fCAL) ( Lamot et al ), emerges as the central event in the early stages of SpA.…”
Section: Overview Of the Issuementioning
confidence: 99%
“…MIF is produced by a wide variety of innate and adaptive immune and non-immune cells [110]. MIF is implicated in several biological functions and may also modulate bone metabolism by promoting both osteoclastic and osteoblastic activity [111][112][113][114][115]. Binding of MIF to CD74 on B cells may induce survival, proliferation, and maturation via NF-κB mediated transcription [116][117][118].…”
Section: Antibodies Directed Against Intracellular Molecules Involved...mentioning
confidence: 99%